The Perspective of Efl Teachers On the Use of Communicative Language Teaching Clt in English Classes in Erbil City - Sangar Lateef Omer (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
There are increasing demand in schools in Erbil city to bring a change to the current ELT teachings, and the academic literature has shown that Communicative Language Teaching English in the classrooms is positively associated with school leaders’ effectiveness at implementing reforms. The purpose of this study is to survey the communicative language teaching CLT in English language teaching classrooms as a foreign language in Erbil city, to bring about change and innovation within this Middle Eastern educational system, and to investigate teachers’ and principals’ overall acceptance of this type of leadership in this country. The methods used to realize in this study involves an initial questionnaire and a detailed follow-up to 27 teachers and principal’s interviews conducted by the researcher. The findings indicate that principals believe they are practicing high levels of Communicative Language Teaching English in the classrooms, but the majority of the teachers have an iconoclastic view with that assessment. This trend emerges from all the components of the Communicative Language Teaching English in the classrooms model that was utilized in the study: challenging the process, inspiring a shared vision, enabling others to act, modeling the way, and encouraging the heart. This realization suggests that Communicative Language Teaching English in the classrooms can still be a success in Erbil city, but modification of that model is suggested.